Knee flexion contracture impacts functional mobility in children with cerebral palsy with various degree of involvement: a cross-sectional register study of 2, 838 individuals. (4th July 2021) - Pantzar-Castilla, Evelina Hanna Sofia; Wretenberg, Per; Riad, Jacques
Abstract : Background and purpose — The impact of knee flexion contracture (KFC) on function in cerebral palsy (CP) is not clear. We studied KFC, functional mobility, and their association in children with CP. Subjects and methods — From the Swedish national CP register, 2, 838 children were defined into 3 groups: no (≤ 4°), mild (5–14°), and severe (≥ 15°) KFC on physical examination. The Functional Mobility Scale (FMS) levels were categorized: using wheelchair (level 1), using assistive devices (level 2–4), walking independently (level 5–6). Standing and transfer ability and Gross Motor Function Classification (GMFCS) were assessed. Results — Of the 2, 838 children, 73% had no, 14% mild, and 13% severe KFC. KFC increased from 7% at GMFCS level I to 71% at level V. FMS assessment (n = 2, 838) revealed around 2/3 were walking independently and 1/3 used a wheelchair. With mild KFC (no KFC as reference), the odds ratio for FMS level 1 versus FMS level 5–6 at distances of 5, 50, and 500 meters, was 9, 9, and 8 respectively. Correspondingly, with severe KFC, the odds ratio was 170, 260, and 217. In no, mild, and severe KFC 14%, 47%, and 77% could stand with support and 11%, 25%, and 33% could transfer with support. Interpretation — Knee flexion contracture is common in children with CP and the severity of KFC impacts function. The proportion of children with KFC rose with increased GMFCS level, reduced functional mobility, and decreased standing and transfer ability. Therefore, early identification and adequate treatment of progressive KFC is important.